2014
DOI: 10.1103/physrevd.90.064051
|View full text |Cite
|
Sign up to set email alerts
|

F(R)nonlinear massive theories of gravity and their cosmological implications

Abstract: We propose a nonlinear massive gravitational theory which includes F (R) modifications. This construction inherits the benefits of the de Rham-Gabadadze-Tolley model and is free of the Boulware-Deser ghost due to the existence of a Hamiltonian constraint accompanied by a nontrivial secondary one. The scalar perturbations in a cosmological background can be stabilized at the linear level for a wide class of the F (R) models. The linear scalar mode arisen from the F (R) sector can absorb the nonlinear longitudin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
87
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(88 citation statements)
references
References 61 publications
0
87
1
Order By: Relevance
“…8 for more details). For simplicity we work within the Einstein frame and expand the metrics using the famous Arnowitt-Deser-Misner (ADM) formalism:…”
Section: Hamiltonian Constraint Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…8 for more details). For simplicity we work within the Einstein frame and expand the metrics using the famous Arnowitt-Deser-Misner (ADM) formalism:…”
Section: Hamiltonian Constraint Analysismentioning
confidence: 99%
“…6 We work in the Einstein frame, using the Lagrangian (6), and then consider perturbations around a homogeneous and isotropic background. 8 The scalar perturbations involve the metric…”
Section: Perturbation Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Another alternative came from the idea that the graviton may have a nontrivial mass as was proposed by Fierz and Pauli [1]. For recent reviews and related f (R) modifications and cosmological models, in general, with non-minimal coupling and dilaton-brane cosmology, local anisotropies and/or effective modeling of massive gravity, see, respectively, [6][7][8][9][10][11][12] and [13][14][15][16][17][18]. The modern version of a ghost-free (bimetric) massive gravity theory was made in a series of papers (recent reviews can be found in [19]): developing generic nonlinear versions of the FierzPauli theory, the so-called vDVZ discontinuity problem was solved via the Vainshtein mechanism [20][21][22] (avoiding the discontinuity by going beyond the linear theory).…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10], it is possible to have a non-linear massive gravity, free of the Boulware-Deser ghost, at the decoupling limit [9] and in the full theory [10]. For some recent works on massive bigravity theories, see [11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%